Guerra conjugal: o cinema antropofágico de Joaquim Pedro de Andrade - Ferreira, Douglas de Magalhães [UNESP] (2015)
The research field in which this work can be inserted in is that of the intricate relations between literature and cinema, and its subject matter is Guerra conjugal (1975), a film adaptation by one of the exponents of Cinema Novo in Brazil, Joaquim Pedro de Andrade, for some short-stories by Dalton Trevisan, one of the most important writers in Portuguese. Taking the adaptive effort as a critical translation and not at all accustomed, therefore, to the requirement of fidelity to the original work, the objective of this research is to demonstrate, by the analysis of the filmic narrative sequence dedicated to the decadent vampire figure of Nelsinho, the anthropophagic orientation that (1), in a positive sense, guides the creative method of the filmmaker Joaquim Pedro, whose work holds closely and fruitful dialogue with the Brazilian literature, but without undergoing the books; and (2), now in a negative way, permeates the loving battles of Guerra conjugal, which characters' intentions are to dominate, to impose, finally, to eat each other through the sexual experience, in a choice that lines up the film to at least two major inclinations of the cinema from that decade: sex as a political banner and the picture of decay through the chronic of private life. To achieve this goal, efforts will be made to identify the short-stories by Dalton Trevisan used for the composition of Nelsinho's path along the film as well as the main literary expedients of the writer from Curitiba, while considering the context of growth of the short-story in Brazil between the decades 1960-1970. Then it will be tried to analyze in details the narrative of the film adaptation, in a way to highlight how Joaquim Pedro translated the short-stories to the screen, rewriting Trevisan's literature in a filmic genre of a broad popular appeal, the pornochanchada, to which recurring features the filmmaker adheres in principle just to subvert them after